Pengaruh Digital Marketing dan Electronic Word of Mouth (E-Wom) terbadap Keputusan Pembelian Pada Produk Fashion Tik-Tok Shop (Survei Pada Mahasiswa Ilmu Komunikasi Universitas Slamet Riyadi Surakarta) - Yudhistira, Muhammad Alamsyach; Itasari, Andri Astuti; Sarungu, Lukas Maserona (Solidaritas, 2024)
ABSTRACTThis research aims to determine the significance of the influence of digitalmarketing and electronic word of mouth (E-WOM) on purchasing decisions forfashion products at the TikTok shop. This type of research is explanatory with surveyresearch methods and data collection using questionnaires and other data such asjournals, books, articles, etc. The population of this research is 100 CommunicationScience Students, Slamet Riyadi University class 2020-2023. The sampling used wasprobability sampling with random sampling technique. The results of the researchshow that digital marketing (X1) and electronic word of mouth (e-wom) (X2) partiallyhave a significant effect on the decision to purchase fashion products at the TikTokshop, with a value of 2,936 with a p-value of 0.004, and electronic word of mouth ( e-wom) obtained a value of 3,866 with a p-value of 0.000. Simultaneously, digitalmarketing and electronic word of mouth (e-wom) have a significant influence on thedecision to purchase fashion products at the TikTok shop for communication sciencestudents at Slamet Riyadi University, with a value of 70,039 with a p-value of 0.000.The coefficient of determination (R2) obtained a value of 0.582, which means thatdigital marketing and electronic word of mouth have an influence of 58.2% onpurchasing decisions and the remaining 42.8% is influenced by other variables thatwere not examined.Keywords : digital marketing, electronic word of mouth (e-wom), decision to purchase